The Origins of Maya States - Traxler, Loa P.; Sharer, Robert J. (Penn Museum international research conferences, 2016)
"Rather than unified into a single state, the Pre-Columbian Maya were organized into a series of independent kingdoms or polities. The vast majority of studies of Maya states focus on the apogee of their development in the Classic period, ca. 250-850 CE. In fact, Maya states are defined by the specific political structures that characterized Classic period lowland Maya society. The Origins of Maya States is the first study in over 30 years to specifically examine the origins and development of these states during the preceding Preclassic period, ca. 1000 BCE to 250 CE. Coverage includes material signatures for the development of Maya states, evaluations of extant models for the emergence of Maya states, and advancement of new models based on recent archaeological data. Attempts to understand the origins of Maya states cannot escape the limitations of archaeological data, and this is complicated by both the variability of Maya states in time and space, and the interplay between internal development and external impacts. To mitigate these factors, The Origins of Maya States combines an examination of topical issues with regional perspectives from both the Maya area and neighboring Mesoamerican regions to highlight the role of interregional interaction in the evolution of Maya states. At the core of the study the development of complexity during the Preclassic era is discussed within the Maya regions of the Pacific coast, highlands, and lowlands. This is followed by studies of Preclassic economic, social, political, and ideological systems to provide a developmental context for the origins of Maya states"--Provided by publisher.